Trainee auditors' perception of ethical climate and workplace bullying in Chinese audit firms - Anthony A. Liu (Emerald Publishing Limited, 2020)
The purpose of this paper aims to investigate the relationship between the audit firm's ethical climate and workplace bullying perceived by trainee auditors in Chinese audit firms.An Ethical Climate Questionnaire and a Negative Acts Questionnaire are adapted from the existing organization studies and business ethics literature to fit in the audit firm context and are administered in a survey on 205 trainee auditors with a four-month long work placement in audit firms. SPSS is used in statistical analyses and tests.This study confirms that some but not all types of organizational ethical climate significantly affect the perceived workplace bullying in audit firms. The results of testing for the relations between workplace bullying and ethical climate after breaking down workplace bullying into the work-related and person-related bullying sub-categories provide some different conclusions. Besides the impacts of the ethical climate on workplace bullying, this paper also finds out that trainee auditor's gender, the leader–subordinate gender difference, firm size and audit engagement team size are more likely to affect the perception of one or more of the bullying categories in audit firms.This study implies some guidance for the audit firms to establish healthy ethical climates that can help them to recruit, train and retain young skilled auditing professionals.The findings of this study imply that a healthy ethical climate can help develop the audit profession and markets by deterring workplace bullying in audit firms.This paper extends the organizational studies on the impact of the audit firm's organizational ethical climate on workplace bullying in the auditing profession. It also extends the gender roles in organization studies by stratifying the levels of workplace harassment.